Analysis on the risk factors of medication-overuse headache in Chinese patients. (February 2018) - Li, Junxia; Chen, Chunfu; Zhang, Ligong; Cui, Xiaochen; Wei, Chuanqiao; Diao, Xiaojun
Highlights: Our study explored the risk factors of MOH in China for the first time. In this clinic-based, case-control study, we found independent risk factors of MOH in Chinese patients. It provided epidemiological reference data for MOH. It will have an impact on the selection of optimal prevention and treatment options. Abstract: Objective: The purpose of this study was to analyze the risk factors of medication-overuse headache in patients with chronic migraine in China. Materials and methods: 157 patients who were diagnosed as chronic migraine were chosen from headache outpatients of Shandong Provincial Hospital affiliated to Shandong University. Based on a standardized questionnaire, a database was developed and analyzed with 45 indexes. Results: The independent risk factors of medication-overuse headache identified in this study included the frequency of medicine overuse (OR = 9.575, 95%CI, 3.573–35.659), Allodynia Symptom Checklist scores (OR = 5.846, 95%CI, 2.065–22.856), anxiety disorder (OR = 2.902, 95%CI, 1.601–7.476) and lack or non- standardized preventive treatment (OR = 1.173, 95%CI, 1.073–3.826). Conclusions: The frequency of medicine overuse, Allodynia Symptom Checklist scores, anxiety disorder and lack or non-standardized preventive therapy were the independent risk factors for medication-overuse headache in patients with chronic migraine.